PENTINGNYA PERIZINAN DALAM PEMBANGUNAN VILLA - Erikson Sihotang (Jurnal Ilmiah Raad Kertha, 2025)
Bali is a province in Indonesia with unique characteristics that contribute toregional development, where economic pillars are built on the strengths of the tourismsector. Its rich natural and cultural potential supports sustainable tourismdevelopment. The extraordinary natural beauty and unique cultural heritage of Balimake it one of the most popular tourist destinations in Indonesia. This view wassupported by Tourism Minister Arief Yahya, who stated that Bali is a destinationalready well-known on the global tourism map. Therefore, Bali is highly deserving ofbeing an icon of Indonesian tourism